Study on the influence of blasting on the structural stability of newly-built and adjacent tunnels - Zi-qiang Li; Jia-shuai Zhang; Gui-quan Ma; Ze-lin Zhou; Sheng-peng Pu; Ceng Zeng (Scientific Reports)
Abstract With the rapid development of urban underground spaces, newly constructed tunnels are being constructed increasingly closer to existing ones. In such cases, blasting may cause overbreak and underbreak, potentially compromising both the structural stability of the new tunnels and the operational safety of adjacent tunnels. In this study, we investigated the double-track tunnel project in Chongqing University Town; the blasting operation was classified into the blasting action period (from the beginning to load termination of blasting) and the overbreak period (from blasting termination to surrounding rock deformation stability). Overbreak and underbreak distribution data were acquired through self-developed blasthole detection devices and laser profile scanners. Using numerical models constructed with LS-DYNA and ANSYS, this study systematically analyzed the dynamic response characteristics of the blasting process of the newly-built tunnel and its effect on the structural stability of adjacent tunnels. Finite element simulation results using intelligent detection data matched the measured excavation contour with over 85% accuracy, revealing the correlation between the blasthole position offset and overbreak position and amount. During the formation period of overbreak in the newly-built tunnels, the section displacement attenuated gradually, and irregular contours increased the tensile stress concentration and rockfall risk. Moreover, uniform overbreak of the entire contour of the section decreased the stress concentration. During the blasting period of the adjacent tunnel, the overbreak and underbreak positions significantly affected the internal force on the lining of the adjacent tunnel. A prominent stress response of the vault and arch bottom was observed. The vibration velocity of the lining of the adjacent tunnel was positively correlated with the contour radius, and was regulated by the loading state at different positions. Therefore, blasting operations in new tunnels should take into account the void position of the adjacent tunnel base. During the formation period of overbreak of the adjacent tunnel, overbreak had a weak influence on the lining displacement, and excavation unloading dominated surrounding rock displacement. The peak stress was concentrated at the center and lower side of the arch foot, and the inner side of the arch bottom experienced tensile stress over a large area. Thus, the positions adjacent to the arch foot and arch bottom of the tunnel should be carefully considered in the construction of new tunnels.